Rural Development Program (RDP): mid year report - BRAC (© BRAC, 2016)
1. Introduction 2. Institution building 3. V. O. fund generation 4. Income and employment generation activities 5. Credit operation 6. Nor-formal primary education 7. Para-Legal Aid Programme (PLAP) 8. Staff development and training 9. Socio-economic implications 10. Concluding remarks